2020
DOI: 10.1371/journal.pone.0232121
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, clinical features, and impact of food habits on the risk of hepatocellular carcinoma: A case-control study in Bangladesh

Abstract: Hepatocellular carcinoma (HCC) is the sixth most common cancer and the third most common cause of cancer mortality worldwide. Infection with hepatitis B virus (HBV) and/or hepatitis C virus (HCV) is the most predominant cause of HCC. Concerns arise for the presence of additional risk factors, as there is still a large proportion of patients without HBV or HCV infection. Previous studies have reported that higher intake of fruits and vegetables and reduced consumption of red/processed meat might play a protecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 58 publications
3
5
0
Order By: Relevance
“…(34) On the other hand, as the most significant contributor to plant sources of NDEA, NDMA and NMAMBA, grains intake (contributed primarily by rice and pasta in this population) was found to be positively linked with HCC, which was in line with two previous case-control studies and a cohort study that identified significantly higher HCC risk in association with a higher level of intake of rice or pasta, (35)(36)(37) with relative risks of HCC ranging from 1.21 for brown rice (37) to 4.34 for total rice consumption. (35) The observed positive associations between NDEA, NDMA, and NMAMBA from plant sources and NPIP with HCC risk should be further investigated in a prospective cohort study. A deeper understanding of the mechanisms of exposure to NMAMBA and HCC development is also needed.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…(34) On the other hand, as the most significant contributor to plant sources of NDEA, NDMA and NMAMBA, grains intake (contributed primarily by rice and pasta in this population) was found to be positively linked with HCC, which was in line with two previous case-control studies and a cohort study that identified significantly higher HCC risk in association with a higher level of intake of rice or pasta, (35)(36)(37) with relative risks of HCC ranging from 1.21 for brown rice (37) to 4.34 for total rice consumption. (35) The observed positive associations between NDEA, NDMA, and NMAMBA from plant sources and NPIP with HCC risk should be further investigated in a prospective cohort study. A deeper understanding of the mechanisms of exposure to NMAMBA and HCC development is also needed.…”
Section: Discussionsupporting
confidence: 90%
“…The positive link between fresh dairy products and HCC we observed was also supported by two large, prospective cohort studies: Participants in the highest tertile of milk intake had a 1.51-fold significantly increased HCC risk compared to the lowest tertile group (P trend = 0.05) in the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort study, (33) and in the Nurses' Health Study (NHS) and Health Professionals Follow-Up Study (HPFS) where a total of 164 HCC cases were identified during up to 32 years of follow-up, higher dairy product intake was associated with an increased HCC risk (HR T3 vs. T1 = 1.85; 95% CI = 1.19-2.88; P trend = 0.009). (34) On the other hand, as the most significant contributor to plant sources of NDEA, NDMA and NMAMBA, grains intake (contributed primarily by rice and pasta in this population) was found to be positively linked with HCC, which was in line with two previous case-control studies and a cohort study that identified significantly higher HCC risk in association with a higher level of intake of rice or pasta, (35)(36)(37) with relative risks of HCC ranging from 1.21 for brown rice (37) to 4.34 for total rice consumption. (35) The observed positive associations between NDEA, NDMA, and NMAMBA from plant sources and NPIP with HCC risk should be further investigated in a prospective cohort study.…”
Section: Discussionsupporting
confidence: 90%
“…The association of fruit and vegetable consumption with HCC progression has been largely confirmed since Negri et al and his team reported it in the 1990s [28]. High amounts of leafy vegetables in the diet, such as spinach and parsley, have been shown to offer protection against HCC [15]. Fruits and vegetables have high levels of minerals, vitamins, fibers, and flavonoids.…”
Section: Diet Has a Direct Effect On The Gut-liver Axismentioning
confidence: 91%
“…A number of studies have reported an inverse correlation between milk [7,8], tea [9], fiber and whole grains [10], white meat [3,11], fruits and vegetables [12,13], and fish [14] and HCC progress. On the contrary, increased consumption of red meat [3,11] positively correlates with HCC risk; whereas studies on HCC risk and egg and rice consumption have reached conflicting results [9,[15][16][17] (Table 1). Discrepancies between studies from different countries could be attributed to differences in the cultural dietary practices, for example, the type of oil used in cooking.…”
Section: Diet Has a Direct Effect On The Gut-liver Axismentioning
confidence: 99%
“…It is well known that daily lifestyle, including physical activity, and lifestyle diseases are correlated with various CVDs, including heart failure [11,12]. Also, colon cancer, prostate cancer, hepatocellular carcinoma, lung cancer, gastric cancer, and breast cancer are related with lifestyle, including food habits and smoking, and lifestyle diseases [13][14][15][16][17][18][19][20]. Thus, many types of CVDs and cancer originate from similar lifestyle and lifestyle disorders, indicating that cancer survivors may experience CVDs and that CVDs survivors may experience cancer.…”
Section: Common Pathway Of Life-style Diseases For Cardiovascular Dis...mentioning
confidence: 99%